Thermal and structural investigation of SnO2/Sb2O3 obtained by the polymeric precursor method - de Melo, Danniely S.; Santos, M. R. C.; Santos, Ieda M. G.; Soledade, L. E. B.; Bernardi, M. I. B.; Longo, Elson [UNESP]; Souza, A. G. (Springer, 2007)
SnO2-based materials are used as sensors, catalysts and in electro-optical devices. This work aims to synthesize and characterize the SnO2/Sb2O3-based inorganic pigments, obtained by the polymeric precursor method, also known as Pechini method (based on the metallic citrate polymerization by means of ethylene glycol). The precursors were characterized by thermogravimetry (TG) and differential thermal analysis (DTA). After characterization, the precursors were heat-treated at different temperatures and characterized by X-ray diffraction. According to the TG/DTA curves basically two-step mass loss process was observed: the first one is related to the dehydration of the system; and the second one is representative to the combustion of the organic matter. Increase of the heat treatment temperature from 500 to 600 degrees C and 700 degrees C resulted higher crystallinity of the formed product.
Keywords: cassiterite; polymeric precursor method; thermal analysis